Spline Computation for Solving Magnetohidrodynamics Free Convection Flow - Hamasalh, Faraidun Kader; G., Joseph; G., Najmadeen (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
In this paper, we construct numerical algorithms for solving Magnetohidrodynamics(MHD) free convection flow rate which has been discussed in detail. It is observed that, for a nonlinear system of differential equation, the spline model of nine degree is used, effectiveness and accuracy of this new method are presented. Several theorems relating the order of the ninth spline to the saturation of the estimator are proved. Some results of consistency are given and an application MHD system is given.